Quality Analysis of Shampoo Based on Rosemary Essential Oil (Rosmarinus officinalis L.) Concentration - Rafika Kumalasari; Amar Ma'ruf; Deni Hendarto; Helmi Haris (Agroindustrial Technology Journal, 2025)
Rosemary essential oil contains components such as camphor, 1,8-cineole, α-pinene, borneol, camphene, limonene, verbenone, caryophyllene, and myrcene. Rosemary oil is widely used in the cosmetics industry due to its fresh aroma and benefits in improving blood circulation, which can support hair growth. Rosemary is more commonly used as a food seasoning and fragrance ingredient, but its potential in hair care products still needs further development. This study aims to obtain the quality of shampoo with the addition of rosemary essential oil according to SNI 8860:2020, determine the most preferred formulation through a hedonic test, and identify the best formulation based on SNI and hedonic tests. The research method was carried out by adding variations in the concentration of rosemary essential oil in formulations X0 (0%), X1 (2%), X2 (4%), and X3 (6%) with two repetitions, with testing based on SNI 8860:2020 and hedonic testing using the Friedman-Conover method. The tests conducted included pH testing, determination of Total Plate Count (TPC), determination of Yeast and Mold Count (YMC), and hedonic tests with parameters such as color, aroma, texture, and comfort. The results showed that the pH values of the four formulations ranged from 6.35 to 6.55. The Total Plate Count values for all four formulations ranged from 5.426 × 10¹ to 7.319 × 10¹ CFU/ml. In the YMC test, all formulations showed negative results, indicating no yeast and mold growth. In the hedonic test, formulation X1 was the most preferred in terms of color and aroma, while formulation X3 was the most favored in terms of texture and comfort. Based on all test results, formulation X1 was concluded to be the best rosemary shampoo formulation.